Synthesis and Dyeing Performance of Acid Dyes Based on N-[3-Hydroxyphenyl]-8-Quinoline Sulfonamide System on Various Fabrics - N. Vashi, Mukesh; G. Mehta, Arvind (Asian Journal of Chemistry, 2010)
N-(3-Hydroxyphenyl)-8-quinoline sulphonamide (II), used as a coupling component, was prepared by the chlorosulfonation of quinoline giving 8-quinoline sulfonylchloride (I) followed by condensation with 3-aminophenol. Fifteen N-(3-hydroxyphenyl-4-R-azo)-8-quinoline sulphonamide acid dyes (IVa–o) were prepared by coupling (II) with various diazo components (IIIa–o). The compounds (IVa–o) were characterized by elemental and spectral analysis and their dyeing performance on silk, wool and nylon fabrics was assessed.